Vibration Disturbance Damping System Design to Protect Payload of the Rocket - Sutisno Sutisno; Andreas Prasetya Adi (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2012)
Rocket motor generates vibrations acting on whole rocket body including its contents. Part of the body which is sensitive to disturbance is the rocket payload. The payload consists of various electronic instruments including: transmitter, various sensors, accelerometer, gyro, the embedded controller system, and others. This paper presents research on rocket vibration influence to the payload and the method to avoid disturbance. Avoiding influence of vibration disturbance can be done using silicone gel material whose typical damping factors are relatively high. The rocket vibration was simulated using electromagnetic motor, and the vibrations were measured using an accelerometer sensor. The measurement results were displayed in the form of curve, indicating the vibration level on some parts of the tested material. Some measurement results can be applied to determine the good material to attenuate vibration disturbance on the instruments of the payload.